Feasibility of using recycled concrete aggregate in dense-graded and gap-graded hot mix asphalts / Mohammad Saeed Pourtahmasb - Mohammad Saeed, Pourtahmasb (2016)

(untitled)
In recent years, several studies have been carried out on the utilization of Construction and Demolition (C&D) wastes in developed countries, particularly the reuse of waste materials in new construction sectors. Both scientists and policy-makers have sought to explore the environmental and economic advantages of waste material recycling. Recycled Concrete Aggregate (RCA), produced from the demolition of concrete structures such as buildings, bridges and dams, is one of the largest wastes in the world in terms of volume. RCAs have different physical, chemical and mechanical properties to natural aggregates. In particular, the porous structure of the concrete and cement paste often attached to the surface of the recycled aggregates can lead to lower abrasion resistance, lower density and higher absorption than virgin aggregates. At the same time, there have been some recent studies showing the successful use of RCA materials in new concrete constructions. Several studies have also been carried out on the possibility of using RCA in base and sub-base either as unbound materials or bitumen-treated or cement-treated granular materials. The present study presents experimental research on the feasibility of utilizing RCAs in stone mastic asphalt (SMA) and hot mix asphalt (HMA) mixtures for pavements. The RCA materials under study were divided into three categories: Fine RCA (F-RCA) containing aggregate particle sizes of 2.36 mm and smaller; Coarse RCA (C-RCA) containing aggregate particle sizes larger than 2.36 mm; and mixtures of F-RCA and C-RCA, called M-RCA. The Marshall mix design method was used to produce HMA and SMA specimens containing various percentages (0%, 20%, 40%, 60% and 80% by the weight of total mix) and sizes (coarse, fine and mix) of RCA. The volumetric and mechanical properties of these various HMA and SMA specimens were then subjected to a series of tests: Marshall Stability (MS), Flow, Density, Voids in Total Mix (VTM), iv Voids Filled with Asphalt (VFA), Voids in Mineral Aggregates (VMA), Resilient Modulus, Loaded Wheel Tracking (Rutting), Indirect Tensile (IDT) Strength, Moisture Susceptibility and finally Flexural Beam Fatigue tests. The outcomes were statistically analyzed using an analysis of variances (ANOVA). The test results indicated that, regardless of the size of the RCA particles, using RCA to replace virgin aggregates increases the binder content needed in both HMA and SMA mixtures. However, they also showed that, despite the significant impact of the RCA content on the volumetric and mechanical properties of the asphalt mixtures, utilizing up to 40% coarse, 80% fine and 40% mixed RCA in SMA, and up to 60% coarse, 50% fine and 60% mixed RCA in HMA, can comfortably satisfy the standard requirements, for pavements in terms of project and traffic volumes. At the same time, as SMA mixtures are highly influenced by their aggregate characteristics, particular care needs to be taken with regard to the properties of SMA mixtures containing RCA to ensure these meet the desired performance criteria.